What is the impact on recruitment of a shortened compared with a standard-length participant information leaflet? PROMETHEUS in IBD-BOOST: study within a trial, a decentralised UK randomised controlled trial - L. Miller; A. Hart; F. Cléirigh-Büttner; C. Arundel; T. Hamborg; S. McGuinness; R. Moss-Morris; A. Parker; C. Relton; I. Stagg; L. Sweeney; V. Wileman; et al. (Trials)
Abstract Background Participant Information Leaflets (PILs) are lengthy and increasingly complex, and could deter research participation. A shortened PIL may be more appealing as it is likely to provide a more a manageable volume of information. Previous research has found that shortened PILs are no less effective for recruitment outcomes, and we deemed it useful to replicate this in an online setting. We also decided to compare retention rates, given the potential for more information to increase participants’ motivation. Aim To evaluate the efficacy of a shortened vs standard-length PIL on trial recruitment and retention rates. Methods This two-arm study within a trial (SWAT) was embedded in a host randomised controlled trial (RCT)—IBD-BOOST. Potential participants were randomised to receive a standard-length or shortened PIL electronically for recruitment to the host RCT. An ethics committee approved potential participants being blinded to this randomisation. Primary outcome: The percentage of SWAT participants receiving the shortened vs standard PIL who were recruited to the RCT. Results Four thousand two hundred one participants were randomised to the standard-length (n = 2099) and shortened (n = 2102) PIL arms. Thirty-four email queries were received about the PILs—18 from those who received the standard and 16 from those receiving the shortened. Seven hundred eight SWAT participants were recruited to the RCT—333 (15.86%) who received the standard-length PIL and 375 (17.84%) who received the shortened (OR = 1.15, (95%CI = 0.98, 1.35), p = 0.09). Retention rates in the RCT were not statistically different between groups. Conclusion We did not find evidence of a significant difference between RCT recruitment and retention rates in participants randomised to the standard-length PIL compared with the shortened. It may be that a shortened PIL has the same effect on recruitment and retention outcomes, providing that the trial does not require extensive information for other reasons (e.g. safety). Therefore, it could be argued that researchers have a choice about how long to make PILs, perhaps with a link to more detail. Alternatively, given that there was no benefit of the shortened PIL, it may be worth comparing written PILs with other methods of conveying information to determine optimal means of encouraging participation and retention in decentralised trials. Host trial registration A randomised controlled trial of supported, online, self-management for symptoms of fatigue, pain and urgency/incontinence in people with inflammatory bowel disease: the IBD-BOOST trial (ISRCTN71618461 on ISRCTN registry).